2008
DOI: 10.1677/joe-07-0498
|View full text |Cite
|
Sign up to set email alerts
|

Changes in angiotensin II type 1 receptor signalling pathways evoked by a monoclonal antibody raised to the N-terminus

Abstract: The extracellular N-terminus of G-protein-coupled receptors may be involved in signalling events. We examined this in the angiotensin II type 1 receptor (AT1-R) using monoclonal antibody 6313/G2, raised against a conserved sequence in the N-terminal domain, and found it evokes inhibitory and stimulatory responses. In rat aortic smooth muscle cell (RASMC) primary cultures, 6313/G2 (2 . 5 mg/ml) inhibited both basal and angiotensin II (Ang II; 10]thymidine incorporation. Exposure to 6313/G2 gave sustained increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Though not affecting angiotensin II binding to the receptor (Barker et al 1993) the antibody directly stimulates aldosterone secretion via the IP3 pathway in rat glomerulosa cells in vitro, though it also blocks PKC activation, apparently by interrupting receptor internalization (Kapas et al 1994. In other studies on rat vascular smooth muscle cells, basal and angiotensin-stimulated tritiated thymidine incorporation into rat arterial smooth muscle cells was inhibited by 6313/G2, inducing a transient increase in intracellular calcium in cultured rat arterial smooth muscle cells, but reducing PKC and MAPK signal transduction (Xiao et al 2008). A short-chain fragment variable of this antibody also blocked AT1 receptor-mediated caspase-3/7 inhibition in breast cancer cells and dose dependently gave significant tumour regression in breast cell xenografts in vivo.…”
Section: Implications For Therapymentioning
confidence: 95%
“…Though not affecting angiotensin II binding to the receptor (Barker et al 1993) the antibody directly stimulates aldosterone secretion via the IP3 pathway in rat glomerulosa cells in vitro, though it also blocks PKC activation, apparently by interrupting receptor internalization (Kapas et al 1994. In other studies on rat vascular smooth muscle cells, basal and angiotensin-stimulated tritiated thymidine incorporation into rat arterial smooth muscle cells was inhibited by 6313/G2, inducing a transient increase in intracellular calcium in cultured rat arterial smooth muscle cells, but reducing PKC and MAPK signal transduction (Xiao et al 2008). A short-chain fragment variable of this antibody also blocked AT1 receptor-mediated caspase-3/7 inhibition in breast cancer cells and dose dependently gave significant tumour regression in breast cell xenografts in vivo.…”
Section: Implications For Therapymentioning
confidence: 95%
“…Uncertainty regarding the antigenic epitopes of the antibodies is a possible reason for the different effects of AT1R-AAs. It has been shown that unlike the agonistic effect of autoantibodies against ECL2, a monoclonal antibody against the N-terminal of AT1R, 6313/G2, inhibited AngII-induced cell proliferation [ 43 ]. Therefore, antibodies generated against different domains of a receptor can exert different modulating effects.…”
Section: Classical Allostery and Classical Allosteric Modulators Of At1rmentioning
confidence: 99%